Application of Bachmann PLC in Wind Turbine Control System - 丁桂林; 叶伟; 颜毅斌 (Kongzhi Yu Xinxi Jishu)
It is significant that the application of PLC in wind turbine control system. This paper introduces the implementation of Bachmann PLC in wind turbine control system, and then analyzes the hardware and software of control system based on Bachmann PLC. Furthermore, the functions and states of main control software as well as failures and alarms of wind turbine are described.